Gesture and Vocabulary Learning in a Second Language. Issue 1 (11th October 2018) - Huang, Xiaoyi; Kim, Nayoung; Christianson, Kiel
Abstract : When introducing new words in a second language (L2), presenting vocabulary with concurrent gestures might facilitate learners' recollection of new words. Previous research has suggested that this gestural advantage might hold only for gestures that overlap with the semantics of the words. Dual coding theory predicts that learners should learn input better when multiple sensory routes act as aids to retrieval. Our research replicated and extended previous studies examining the limits of gestures in learning L2 vocabulary. A within‐participant design directly compared the effects of pairing low idiosyncratic gestures (gestures traditionally iconic with word meanings) versus high idiosyncratic gestures (gestures that likely need to be idiosyncratically paired with word meanings) with L2 vocabulary presentation, relative to using no gestures. Results supported dual coding theory: All gestures were helpful if they were not confusable with other to‐be‐learned words and if the number of words presented was limited. Open Practices: This article has been awarded an Open Data badge. All data are publicly accessible via the Open Science Framework athttps://osf.io/4awze . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki . Abstract :